ChemInform Abstract: Electrodes Functionalized with the 2, 2, 6, 6‐Tetramethylpiperidinyloxy Radical for the Waste‐Free Oxidation of Alcohols. Issue 16 (April 2015) - Ciriminna, Rosaria; Palmisano, Giovanni; Pagliaro, Mario
Abstract Review: 35 refs.